1999
DOI: 10.1385/abab:81:1:35
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Microbial Inulinases: Its Production, Properties, and Industrial Applications

Abstract: Microbial inulinases are an important class of industrial enzymes that have gained much attention recently. Inulinases can be produced by a host of microorganisms, including fungi, yeast, and bacteria. Among them, however, Aspergillus sp. (filamentous fungus) and Kluyveromyces sp. (diploid yeast) are apparently the preferred choices for commercial applications. Among various substrates (carbon source) employed for their production, inulin-containing plant materials offer advantages in comparison to pure substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
2
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(143 citation statements)
references
References 69 publications
2
135
2
4
Order By: Relevance
“…This finding was in agreement with Pandey, et al [22] who found that inulin-containing plant materials were superior to pure substrates for inulinase production. Inulin has also been reported to be the best carbon source for the pro-…”
Section: Optimization For Inulinase Production By Streptomyces Sp Cp01supporting
confidence: 93%
“…This finding was in agreement with Pandey, et al [22] who found that inulin-containing plant materials were superior to pure substrates for inulinase production. Inulin has also been reported to be the best carbon source for the pro-…”
Section: Optimization For Inulinase Production By Streptomyces Sp Cp01supporting
confidence: 93%
“…Chen et al(1997) purified the inulinase of A. niger using precipitation with ammonium sulphate, DEAE Cellulose and Sephadex G-100 with 67 fold purification, in this case, however, the yield was lower (25.5%) than obtained in the present study (53.63%). Derycke and Vandamme (1983), Cruz et al(1998) and Pandey et al(1999) descried that for industrial application, inulinase showed have maximum activity at pH lower than 5.0 and at higher temperatures, as produced by A. niveus 4128URM. Under these conditions bacterial contamination is rare, solubilization of inulin is favored and fructose syrup coloring is not presented.…”
Section: Partial Purification Of Inulinasementioning
confidence: 99%
“…Fructose formation from inulin offers advantage as it involves only a single enzymatic step yielding up to 95% fructose (Vandamme and Derycke, 1983;Pandey et al, 1999). Inulinases of many microorganisms, especially of filamentous fungi, are used to optimize process of hydrolysis of the inulin related to food industries for the production of alcohol, acetone and butanol (Zittan, 1981;Vandamme and Derycke, 1983;Pandey et al, 1999); are also used in the medical area as a tool for the diagnosis of renal problems (Kuehnle et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las inulinasas microbianas tienen muchas aplicaciones, incluyendo la producción industrial de jarabes de alto contenido de fructosa (JACF), inulooligosacáridos, etanol, aceite y proteína unicelular; y la producción de algunos químicos tales como alcoholes, ácido cítrico y ácido láctico (Castillo y Chamy 2010;Chi et al, 2011;Kango y Jain, 2011). La D-fructosa está en una posición importante en el mercado mundial como edulcorante, ya que ofrece varias ventajas, incluyendo -pero no limitando a -su presencia natural en la mayoría de las frutas (azúcar libre) y en varias plantas (polímero), su poder edulcorante más alto, su metabolismo fisiológico en el cuerpo humano, y sus efectos insulinogénicos insignificantes (Pandey et al, 1999;Ricca et al, 2007). Por consiguiente, las inulinasas microbianas desempeñan un rol importante en la hidrólisis de la inulina para su explotación comercial.…”
Section: Introductionunclassified